Moult migration of Northwest Mainland European Whooper Swans Cygnus cygnus - Stenschke, Nico; Degen, Axel; Schonert, Axel (Wildfowl, 2019)
Moult migration routes taken by non-breeding individuals from the Fennoscandian subpopulation of the Northwest Mainland European Whooper Swan Cygnus cygnus population were determined by tracking swans fitted with data loggers in Lower Saxony, Germany, during 2014. Depending on their origin, the swans flew between a few hundred and many thousands of kilometres (maximum distance: 2,323 km), to reach moulting sites in the Russian Arctic (at latitudes above 66.57°N) within the Nenets Autonomous Okrug and the Yamalo-Nenets Autonomous Okrug. The stages (distance travelled without stopping) of the moult migration were typically far shorter (mean ± s.d. = 34.9 ± 39.6 km) than those flown during spring migration (114.1 ± 133.4 km) or on autumn migration (204.6 ± 248 km). The mean flying height during moult migration (52.1 ± 47.6 m) also differed from that recorded in spring (146.8 ± 136.9 m) and autumn migrations (280.1 ± 350.5 m).